Twelve steps to a compassionate life [large type] - Armstrong, Karen, 1944- (Thorndike Press large print nonfiction, 2011)
Shares practical recommendations for promoting world peace by cultivating one's intrinsic tendencies for compassion, outlining a program for achieving mindfulness and engaging in acts of kindness.